BOUNDARY DEMARCATION FOR A NEW STATE IN INTERNATIONAL LAW - HUSEIN KOKHA, DR. AYAD YASIN (Journal of Duhok University, 2019)
Boundary demarcation is one of the most important aspects of creating new states in the course of international public law. This issue is dealt with through two main problematic areas: on one hand, the existence of uti possidetis due to the phenomenon of colonialism, regarded as the rule of law (jus cogens), which is still valid to the present, and which causes many conflicts (particularly depriving indigenous peoples of their original boundaries). On the other hand, there is no obvious legal rule to bind concerned states to make a demarcation, and the laxity or non-control of a boundary creates a source of tension and a security threat for connected countries. This research mainly aims to render the boundary as a source of stability through encouraging the newly independent states to achieve the demarcation process as soon as possible, thus avoiding all relevant disputes. The findings of the paper show that it is necessary to provide adequate discretionary powers to the Joint Demarcation Commission (JDC)s, specifically those of new States, to overcome obstacles and difficulties for accomplishing demarcation’s practical steps accurately and in a sophisticated manner. Moreover, there are alternatives able to settle related disputes peacefully, in order to stabilise new countries, strengthen them, establish their infrastructures, and evolve cooperation relations based on good neighbourliness among respective states. Eventually, this will contribute to the maintenance of international peace and security